SIMULTANEOUS ELECTROCOAGULATION - PHOTOCATALYTIC SCENARIO TO ENHANCE HYDROGEN PRODUCTION IN LIQUID WASTE TREATMENT: A BRIEF OVERVIEW - Reno Pratiwi; Slamet Slamet; Dina Asmaul Chusniyah; Widia Yanti (Universitas Trisakti, 2022)
The issue of environment and sustainable energy are two issues that have not been completely resolved until today. Liquid waste treatment technology, which can remove pollutants and produce hydrogen gas, is interesting to study since hydrogen itself is one of the energy sources whose use has begun to be developed. Aim: The following article will discuss several aspects that can be developed in each technology. Methodology and Results: Electrocoagulation and photocatalyst are both technologies which are possible to eliminate liquid pollutants while producing hydrogen in a single process. Research that attempts to combine two processes to improve the ability to treat pollutants in wastewater while producing hydrogen has been carried out. The optimization process can be carried out respectively in terms of electrocoagulation and photocatalytic technology. Modifications can also be made by combining the two processes of electrocoagulation and photocatalysis, either sequentially or simultaneously. Modification process carried out aims to increase hydrogen recovery without neglecting the ability of electrocoagulation and photocatalysis in removing organic waste. Conclusion, significance, and impact of study: This brief review provides an overview of the potential of electrocoagulation and photocatalysis technology in its ability to remove liquid waste while producing hydrogen gas. The opportunity to combine the two processes is also shown based on previous studies. The review is carried out based on an in-depth study of the research that has been done. The simultaneous use of both processes has been shown to provide much better capabilities in terms of removing liquid waste and producing hydrogen gas.